PENGARUH MENGUNYAH NANAS (ANANS COMOSUS) TERHADAP SKOR PLAK PADA SISWA KELAS IX SMP NEGERI 1 MARTAPURA TIMUR - Fitri, Aida; Habibah, Siti Sab’atul; Naning, Naning KU; Sari, Emilda (Poltekkes Kemenkes Banjarmasin, 2024)
Abstract: Plaque left untreated can lead to the occurrence of dental caries and tartar, which is a hardened form of plaque. Plaque control can be attained through a combination of mechanical and chemical methods, such as chewing fresh and fibrous fruits. Fruits are good for dental and oral health and also serve as natural cleaners for teeth. Data from the Martapura East Community Health Center indicates a relatively high incidence of dental caries at SMP Negeri 1 Martapura East based on the results of sampled students examined. Out of 140 students examined, 81 students were found to have dental caries. This study aims to determine the effect of chewing pineapple (Ananas Comosus) on Plaque scores among Grade IX students at SMP Negeri 1 Martapura East. This type of research is a quasi-experimental study with a pre-test post-test one group design. The sample was taken using Total Sampling Technique with a sample size of 45 students. This study uses statistical tests, namely the Paired Sample T-test. The research results showed that the average Plaque score before chewing pineapple (Ananas Comosus) was 3.61, and after chewing pineapple, it was 1.42, with an average decrease in Plaque score of 2.19. The paired sample t-test indicates that the null hypothesis is rejected, thus accepting the alternative hypothesis , indicating an influence before and after chewing pineapple. In conclusion, there is an effect before and after chewing pineapple (Ananas Comosus) on Plaque scores among Grade IX students at SMP Negeri 1 Martapura East. It is recommended to chew pineapple as often as possible to reduce Plaque scores, as pineapple serves as an alternative to clean food from the tooth surface.